KONSEP MANUSIA IDEAL DALAM PEMIKIRAN PENDIDIKAN ISLAM DAN IMPLEMENTASINYA PADA TUJUAN PENDIDIKAN NASIONAL - Sultan, Sultan; Damayanti, Ina (Al-Rabwah, 2025)
Education plays a fundamental role in shaping human character and holistic personality. In Islamic education, the ultimate goal is to realize insan kamil the perfect human being who maintains balance between spiritual, intellectual, and moral dimensions. Meanwhile, the Indonesian national education system, as stated in Law Number 20 of 2003 on the National Education System, also emphasizes the formation of a whole person who is faithful, pious, knowledgeable, and responsible. This study aims to analyze the concept of the ideal human in Islamic educational thought and its implementation in Indonesia’s national education objectives. Using a library research method with a descriptive-analytical approach, this study draws upon classical Islamic texts, scholarly journals, and official educational documents. The findings reveal that the concept of insan kamil in Islamic education is substantially aligned with the goals of national education, particularly in fostering harmony between faith, knowledge, and morality. Implementation of this concept can be realized through the integration of spiritual values into the curriculum, strengthening of character education, and enhancing teachers’ competence in internalizing religious values. This study highlights the importance of synergy between Islamic values and the philosophy of national education in developing a generation that is faithful, knowledgeable, ethical, and competitive as the foundation for national progress.